2018
DOI: 10.3390/scipharm86030029
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects and Killing Kinetics of Lactic Acid Rice Gel Against Pathogenic Bacteria Causing Bovine Mastitis

Abstract: and are the major teat skin bacteria and lead to severe bovine mastitis. Teat antiseptic is an important tool for controlling intramammary infection. The antibacterial activity of lactic acid (LA) against one reference strain of ATCC 25923 and two field strains including and was investigated using the broth microdilution method. Its minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were 0.5% for strains belonging to both species. An antiseptic preparation containing 5% LA with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Human sweat contained approximately 0.1% lactate [32]. In this study, we utilized the 0.02% sodium l -lactate for S. epidermidis fermentation (Figure 1) since the higher sodium l -lactate may exert a toxic effect on the bacterial growth [33]. Lactate is fermented to acetate and propionate by various bacteria including Propionibacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Human sweat contained approximately 0.1% lactate [32]. In this study, we utilized the 0.02% sodium l -lactate for S. epidermidis fermentation (Figure 1) since the higher sodium l -lactate may exert a toxic effect on the bacterial growth [33]. Lactate is fermented to acetate and propionate by various bacteria including Propionibacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LA antimicrobial action is known to be strongly dependent on the concentration of the acid and on the pH under which the experiment is carried out [70]. Some authors [16,25] demonstrated that under low pH, the biocide permeabilizes the outer membrane of Gram-negative bacteria. It was suggested that LA acts as a protonator of anionic components like the carbonyl and phosphate groups and consequently, the molecular interactions between components within the membrane are weakened [25,71].…”
Section: Discussionmentioning
confidence: 99%
“…Organic acids and quaternary ammonium compounds (QACs) are among the different classes of biocides that are widely used [16,17,18,19,20,21]. Organic acids are a class of disinfectants particularly used in the food industry [9,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…[21] and Chotigarpa et al . [22]. Briefly, the modified rice powder was used for gel base preparation and viscosity building agent.…”
Section: Methodsmentioning
confidence: 99%